Republic of Poland : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
Poland's outstanding economic performance has come under strain. Executive Directors stressed the need to strengthen fiscal and monetary policies, and accelerate structural reforms. They considered that the new strategy will strengthen the medium-term economic performance, and place Poland in a strong position to secure accession to the European Union. They commended the soundness of the financial system as reported in the Financial Sector Stability Assessment, and agreed that the country's statistical base is adequate for surveillance.